PREDIKSI FINANCIAL DISTRESS PADA KOPERASI DI KABUPATEN PEMALANG - Sukirno, Sukirno; Haryadi, Haryadi; Budiarti, Laeli (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2014)
This paper examines the usefulness of financial statements to predict financial distress in thecooperative. The financial distress is a condition before the bankruptcy that can be seen inthe financial statements. Furthermore, the financial statements are being analyzed using ratioanalysis. The ratio analysis Â used as a predictor variable are current ratio, quick ratio, currentassets to total assets ratio, current liabilities to total assets, net profit margin ratio and net SHUto total assets ratio. While the research object is a cooperative financial statements reported on2012. There are 63 cooperatives used as the sample with purposive sampling approach. Thehypothesis is analysed using logistic regression. The results found that three variables can beÂ used to predict financial distress of the cooperative. Those variables are ratio of current assetsÂ to total assets, current liabilities to total assets and net SHU to total assets. This implies theusefulnes of financial ratio to predict financial distress in the cooperative.